Key concepts that people need to understand to assess claims about treatment effects. Issue 3 (August 2015) - Austvoll‐Dahlgren, Astrid; Oxman, Andrew D.; Chalmers, Iain; Nsangi, Allen; Glenton, Claire; Lewin, Simon; Morelli, Angela; Rosenbaum, Sarah; Semakula, Daniel; Sewankambo, Nelson
Abstract Objective People are confronted with claims about the effects of treatments and health policies daily. Our objective was to develop a list of concepts that may be important for people to understand when assessing claims about treatment effects. Methods An initial list of concepts was generated by the project team by identifying key concepts in literature and tools written for the general public, journalists, and health professionals, and consideration of concepts related to assessing the certainty of evidence for treatment effects. We invited key researchers, journalists, teachers and others with expertise in health literacy and teaching or communicating evidence‐based health care to patients to act as the project's advisory group. Results Twenty‐nine members of the advisory group provided feedback on the list of concepts and judged the list to be sufficiently complete and organised appropriately. The list includes 32 concepts divided into six groups: (i) Recognising the need for systematic reviews of fair tests, (ii) Judging whether a comparison of treatments is fair comparison, (iii) Understanding the role of chance, (iv) Considering all the relevant fair comparisons, (v) Understanding the results of fair comparisons of treatments, (vi) Judging whether fair comparisons of treatments are relevant. Conclusion The concept list provides a starting point for developing and evaluating resources to improve people's ability to assess treatment effects. The concepts are considered to be universally relevant, and include considerations that can help people assess claims about the effects of treatments, including claims that are found in mass media reports, in advertisements and in personal communication.